Effect of High Density Polyethylene on Inflammatory Responses in Wistar Rats (Rattus norvegicus) - Talitha Maurilla Zulkarnain; Isa Ma’Rufi; Candra Bumi (Universitas Pahlawan Tuanku Tambusai, 2026)
Microplastics were a newly emerging type of environmental pollutant composed of plastic particles with a diameter of less than 5 mm. The use of plastic food containers, plastic packaging, and plastic bottles could lead to direct contact and contamination of plastic into food. Microplastics were particles that could not be degraded by phagocytes, allowing inflammation to persist chronically and potentially cause organ dysfunction.The objective of this study was to analyze the effect of oral administration of various doses of HDPE microplastics on neutrophil levels in Wistar rats (Rattus norvegicus). The research method was an experimental study with a post-test only control group design, consisting of one control group and three treatment groups. Neutrophil levels in Wistar rats were measured using an automatic hematology analyzer. The results of neutrophil measurements were analyzed using the Kruskal–Wallis test followed by the Bonferroni post hoc test.The the research results indicate the highest neutrophil levels were observed in the treatment group receiving the highest dose of 0.4 mg/kg/day (X3). The Krus kal–Wallis test yielded a p-value of 0.000 < 0.05, indicating a significant effect among the treatment groups receiving various doses of orally administered HDPE microplastics on the neutrophil levels of Wistar rats.